Climate variability analysis over the state of Himachal Pradesh, India - Priyanka Jattan; Dr. Mohan Singh Jangra; Dr. SK Bhardwaj (International Journal of Climate Conditions, 2026)
Longterm daily temperature and rainfall data (2000–2024) for thirty-five locations ranging from ~350 to >4000 m amsl were obtained from the NASA POWER database. The variability and trends in maximum, minimum temperature and rainfall were worked out by using different statistical tools and Mann-Kendal test trend analysis. The mean annual maximum temperature of the state was 20.3°C (CV = 3.9%), declining from 27.4°C in the low hills to 7.2°C at high elevations, and exhibited a consistent increasing trend, with comparatively higher warming rates at higher altitudes (~0.10°C yr⁻¹) than in the lower (~0.01°C yr⁻¹). Seasonal pooled summer and monsoon maximum temperatures were 22.7°C and 25.5°C, respectively, both showing positive trends. The variability in minimum temperature increased markedly to 21.0 % in the cold-desert belt compared with 3.5 % in the low hills, indicating that night-time temperatures are more sensitive to topographic and synoptic controls than daytime temperatures.Rainfall variability increased from 22.2 % in the mid-hills to 33.1 % above 2500 m, indicating highly unreliable moisture availability in the trans-Himalayan region.The expected outcomes of this research offer important benefits for farmers, planners and other stakeholders in Himalayan agriculture.
Keywords: Himachal Himalayas; Variability; rainfall; temperature; trends